Effect of tannic acid on skin barrier function. Issue 8 (9th January 2018) - Nakamura, Tomoya; Yoshida, Naoki; Yasoshima, Mitsue; Kojima, Yoshihiko
Abstract: In this study, we investigated how tannic acid (TA) protects the skin from inflammation caused by external irritation. The effects of TA were evaluated using a mouse 12‐ O ‐tetradecanoylphorbol 13‐acetate (TPA)‐induced skin inflammation model and a reconstructed human epidermal model. We then used Lucifer Yellow for visual confirmation of TA's suppression effect at the stratum corneum (SC) surface. TA treatment of the skin prevented Lucifer Yellow from permeating the skin. This result suggests that TA acts as a barrier against external stimulants such as TPA and artificial sweat on the SC surface.